Osteocalcin, vascular calcification, and atherosclerosis: a systematic review and meta-analysis - Millar, Sophie A.; Patel, Hinal; Anderson, Susan I.; England, Timothy J.; O'Sullivan, Saoirse (Frontiers, 2017)
Background: Osteocalcin (OC) is an intriguing hormone, concomitantly being the most abundant non-collagenous peptide found in the mineralized matrix of bone, and expanding the endocrine function of the skeleton with far reaching extra-osseous effects. A new line of enquiry between OC and vascular calcification has emerged in response to observations that the mechanism of vascular calcification resembles that of bone mineralisation. To date, studies have reported mixed results. This systematic review and meta-analysis aimed to identify any association between OC and vascular calcification and atherosclerosis.